Complete Mitochondrial Genome of Phytophthora nicotianae and Identification of Molecular Markers for the Oomycetes - Yuan, Xiaolong; Feng, Chao; Zhang, Zhongfeng; Zhang, Chengsheng (Frontiers in Microbiology, 2017)
Phytophthora nicotianae is one of the most destructive plant pathogens affecting a variety of plants, causing black shank of tobacco, among several other devastating diseases. Herein, we assembled the mitochondrial genome of P. nicotianae and analyzed its gene content and genome structure, performed comparative mitochondrial genomics analysis, and assessed phylogenetic relationships among oomycetes species. The circular mitogenome is 37,561 bp long, with 38 protein-coding genes, 25 transfer RNA (tRNA) genes, and 2 ribosomal RNA genes (rrnl and rrns). The mitochondrial genome showed a biased A/T usage versus G/C. The overall gene content and size of the P. nicotianae mitogenome are identical to those of other published Phytophthora mitogenomes. Interestingly, collinearity analysis using an existing ~10k inversion region (including 11 genes and 8 tRNAs) revealed that Phytophthora andina, Phytophthora infestans, Phytophthora mirabilis, Phytophthora ipomoeae, and Phytophthora phaseolis differed from Phytophthora nicotianae, Phytophthora sojae, Phytophthora ramorum, and Phytophthora polonica. Moreover, inverted repeat regions were found to be absent among species of the Peronosporales when compared with species from the Pythiales and Saprolegniales. A phylogenomic investigation based on 29 protein-coding genes demonstrated that Phytophthora is monophyletic, and placed P. nicotianae close to the clade including P. mirabilis, P. ipomoeae, P. andina, P. infestans, and P. phaseoli. Furthermore, we discovered six new candidate DNA molecular markers (rpl6, atp8, nad11, rps2, rps3, and rps4) based on these mitogenomes that would be suitable for species identification in the oomycetes, which have the same identification level as the whole mitogenome and ribosomal DNA sequences. These new molecular markers can not only provide a quick preview of the species without mitogenome information, but will also help to gain better understanding of the oomycetes pathogens and developing treatment or monitoring strategies.